Using mental health and education data for research and policy insights: A ten-year retrospective of a South London data linkage - Wickersham, Alice; Downs, Johnny (International Journal of Population Data Science, 2026)
Since 2015, South London and Maudsley NHS Foundation Trust (London, United Kingdom) has maintained a data linkage between its de-identified Child and Adolescent Mental Health Services records and the Department for Education’s National Pupil Database. Most recently refreshed up to the 2023/24 academic year, this linkage is used to conduct population and clinical research spanning mental health and education. In this presentation, we will outline the linkage’s evolution, including governance and data-sharing frameworks that we have navigated, changes encountered in the decade since its original formation, and key learnings. We will discuss public engagement activities we have undertaken around the linkage, including novel approaches to directly involve children and young people in complex analytical decisions. Finally, we will showcase the wide array of research that has arisen from this linkage, spanning depression, Attention-Deficit/Hyperactivity Disorder (ADHD), educational attainment, special educational needs support, and more. Many of our findings have informed policymakers. Our most recent study replicates a longitudinal analysis first conducted in Norway, showing diminishing associations between ADHD and end-of-school exam performance. This demonstrates how the growing availability of data linkages permits international research replication. By identifying overlapping trends, countries can work jointly on policy solutions in full confidence that many of us are grappling with the same challenges, despite having mental health and education systems that diverge operationally. In the decade since its inception, this linkage has exemplified how administrative data drives research and policy, and there is greater opportunity than ever before for global collaboration.